Dampak Peer Review dan Lecturer Corrective Feedback pada Kinerja Penulisan Artikel Ilmiah Mahasiswa - Umiyati Jabri; Ismail Ismail (Universitas Muhammadiyah Enrekang, 2021)
. The current research is expected to contribute to guiding students' scientific work by providing opportunities for them to correct the lack of understanding when they carry out their research assignments. This study uses qualitative and quantitative approaches (mixed method) which aims to investigate whether the use of peer reviews and lecturer corrective feedback has a positive effect on the performance of writing scientific articles for students as novice writers. Study participants included one class of a total of 18 students in the English Education Department. The Likert scale is used to measure the level of ability and benefits of peer review feedback and lecturer corrective feedback in writing scientific article skills based on student perceptions. The data revealed that the majority of the revisions made by students were the revision of the meaning surface (Meaning-level revisions) of 4258 (72.46%) for 4 times the revision of the draft article. Revisions to the level of change of meaning gradually result in an improvement of the articles as a whole before submitting the final draft of their article. In terms of students' perceptions of the application of peer review and corrective feedback in the learning process, students expressed a positive attitude. This study shows the importance of assessing the peer-review process in writing scientific papers